Pengaruh Belanja Hibah dan Belanja Bantuan Sosial terhadap Tingkat Kemiskinan melalui Pertumbuhan Ekonomi di Kota Jambi periode tahun 2001-2019 - Rizki, Ita; Zulgani, Zulgani; Hodijah, Siti (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2023)
This study aims to: 1) To analyze the development of grant spending and social assistance spending on poverty levels through economic growth in Jambi City during 2001-2019. 2) To analyze the effect of grant spending and social assistance spending on economic growth in Jambi City during 2001-2019. 2019.3) To analyze the effect of grant spending and social assistance spending on poverty levels through economic growth in Jambi City during 2001-2019. The research model used in this study is the Path Analysis model. The contribution of the influence of Grant Expenditure and Social Aid Expenditure on Economic Growth in Jambi City during the period 2001-2019 simultaneously has an effect on economic growth. While partially the two independent variables, namely grant spending has a negative effect on economic growth and the social assistance expenditure variable has a positive and significant impact on economic growth in Jambi City.The contribution of the influence of Grant Expenditure and Social Aid Expenditure on the poverty level through economic growth in Jambi City during the period 2001-2019 can be concluded that the independent variables of Grant Expenditure and Social Aid Expenditure simultaneously have a positive and significant effect on the poverty level through the intervening variable, namely economic growth.